Occurrence of Oxyruncus cristatus (Swainson, 1821), Sharpbill (Aves, Oxyruncidae), in the Belem area of endemism and first records from Maranhão, Brazil - Luis Aguiar de Morais; Flávio Kulaif Ubaid (Check List, 2022)
We document the first record of Oxyruncus cristatus Swainson, 1821, Sharpbill, in the Brazilian state of Maranhão. This represents the first documented occurrence of this species in the Bélem area of endemism. The species was monitored in a fragment of lowland forest where it remained throughout the year, contradicting the altitudinal migrations described for the Amazonian subspecies, O. c. tocantinsi Chapman, 1939. It is possible that migratory movements are facultative in O. cristatus, or even that extensive deforestation can suppress migratory behavior, based in scattered records.